2018
DOI: 10.1111/jmwh.12706
|View full text |Cite
|
Sign up to set email alerts
|

Certified Nurse‐Midwives’ Knowledge, Attitudes, and Behaviors About Infant Safe Sleep

Abstract: Certified nurse-midwives routinely provide guidance on infant care, and it is important that they are familiar with current evidence-based recommendations on infant safe sleep. They should be supported in their desire to provide infant safe sleep education to their prenatal patients. In addition, efforts should be made to improve attitudes and social norms related to providing infant safe sleep education in the prenatal environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Multiple previous studies have examined issues with the operation of facilities, such as facility management and the establishment of emergency contact networks [14], and overall practices at daycare facilities [15,16]. These previous studies support the need for compliance with SSP among caregivers, including daycare personnel, mothers, and health professionals, and knowledge and confidence related to SSP are asso-ciated with the performance of SSP [17][18][19]. A better understanding of SSP may contribute to improvement in the quality of sleep environments in the childcare field.…”
Section: Introductionmentioning
confidence: 80%
“…Multiple previous studies have examined issues with the operation of facilities, such as facility management and the establishment of emergency contact networks [14], and overall practices at daycare facilities [15,16]. These previous studies support the need for compliance with SSP among caregivers, including daycare personnel, mothers, and health professionals, and knowledge and confidence related to SSP are asso-ciated with the performance of SSP [17][18][19]. A better understanding of SSP may contribute to improvement in the quality of sleep environments in the childcare field.…”
Section: Introductionmentioning
confidence: 80%
“…Third, pediatric nurses' confidence in delivering education on a safe sleep environment and confidence in SSSP was a mean of 2.6 on a 1~5 scale, which is considered as fairly low confidence. In the study conducted by Hodges, Anderson, McKenzie, and Katz [26], 82% of nurse-midwives responded that they were confident in carrying out their work duties related to a safe environment. As well, in the study of Kacho [15], 64% of nurses responded that they were confident when they delivered anticipatory guidance on expanded back-tosleep guidelines and practices.…”
Section: Chnrmentioning
confidence: 99%
“…No previous studies have broadly explored midwives’ and other perinatal health workers’ perspectives on Black maternal mortality. Previous studies of US midwives’ attitudes, perceptions, and beliefs have focused elsewhere, for example, on newborn screenings, 10 men in midwifery, 11 infant safe sleep, 12 and planned home birth 13 . Almanza et al identified the motivations of 7 midwives of color—their strong commitments to racially concordant care, racial justice, and physically and emotionally safe care—associated with an African American‐owned community birth center 14 .…”
Section: Introductionmentioning
confidence: 99%